New ALMA constraints on the star-forming interstellar medium at low metallicity: a 50 pc view of the blue compact dwarf galaxy SBS 0335−052. (28th February 2017) - Cormier, D.; Bendo, G. J.; Hony, S.; Lebouteiller, V.; Madden, S. C.; Galliano, F.; Glover, S. C. O.; Klessen, R. S.; Abel, N. P.; Bigiel, F.; Clark, P. C.
Abstract: Properties of the cold interstellar medium of low-metallicity galaxies are not well known due to the faintness and extremely small scale on which emission is expected. We present deep ALMA band 6 (230 GHz) observations of the nearby, low-metallicity (12 + log (O/H) = 7.25) blue compact dwarf galaxy SBS 0335−052 at an unprecedented resolution of 0.2 arcsec (52 pc). The 12 CO J = 2→1 line is not detected and we report a 3σ upper limit of L CO(2–1)  = 3.6 × 10 4  K km s −1  pc 2 . Assuming that molecular gas is converted into stars with a given depletion time, ranging from 0.02 to 2 Gyr, we find lower limits on the CO-to-H2 conversion factor αCO in the range 10 2 –10 4  M⊙  pc −2 (K km s −1 ) −1 . The continuum emission is detected and resolved over the two main super star clusters. Re-analysis of the IR–radio spectral energy distribution suggests that the mm-fluxes are not only free–free emission but are most likely also associated with a cold dust component coincident with the position of the brightest cluster. With standard dust properties, we estimate its mass to be as large as 10 5  M⊙ . Both line and continuum results suggest the presence of a large cold gas reservoir unseen in CO even with ALMA.